Phenomenological Research in Art Studies: A Robust Framework for Aesthetic Inquiry - Sunarto, Bambang; Yulika, Febri (Harmonia: Journal of Arts Research and Education, 2025)
This article examines aesthetic experience as a central focus in art research, a field complicated by its inherent subjective and objective dimensions. It proposes a phenomenological methodological framework designed to balance the objective analysis of artworks with a subjective understanding of individual experience. The recommended methods are grounded in core phenomenological principles, including an emphasis on lived experience, the application of epoché (the bracketing of preconceptions), phenomenological reductions for uncovering essences, and the description of essential experiences. The article demonstrates that phenomenological approaches can systematically accommodate the depth of subjective experience and the personal nature of art, while maintaining the analytical rigor essential for academic research. Notably, this article presents a coherent methodological approach for examining aesthetic experience, effectively bridging the gap between scientific rigor and aesthetic sensibility, and thereby fostering a richer, deeper understanding of how art is experienced and interpreted.